Change of some characteristics of HDPE pipes tested in Nghe An province seawater. Issue 2 (24th April 2020) - Chinh, Nguyen Thuy; Hiep, Nguyen Anh; Thang, Dam Xuan; Trang, Tran Do Mai; Hoang, Thai
Abstract: This paper focuses to study on change of some characteristics of high density polyethylene (HDPE) pipes testing in Nghe An province seawater. The investigated characteristics of HDPE pipe before and after testing are structural, morphological, crystal, thermal property and stability. Infrared (IR) spectroscopy, scanning electron microscope (SEM), X‐ray diffraction (XRD), thermogravimetric analysis (TGA) and differential thermal analysis (DTA) methods were used to evaluate the change in characteristics of PE pipes after 10 testing months in Nghe An province seawater. In addition, the change in weight and tensile properties of PE pipes after testing was also investigated. The obtained results showed that the Nghe An province seawater had an influence on the structural, morphological, tensile, crystal and thermal characteristics of PE pipes.